An Analysis of the Quality of Patient Development Integrated Records as System Information Among Healthcare Professionals - Muhammad Hadi (Journal of Global Pharma Technology, 2020)
Patient Development Integrated Records (CPPT) is the documentation for health personnel in conducting the assessment of hospitalized patients according to the Hospital Accreditation Committee Standard (KARS). The CPPT is a tool for all health professions to convert the data and treatment plan for the patient. This would lead to a collaboration and communication between healthcare professionals at the hospital. This study aims to analyze CPPT as the information system between healthcare professionals at the hospital. This design study used a mixed-method with quantitative research as a source of primary data and qualitative research as secondary data. This research used cross-sectional approach as the quantitative tool, involving 76 health workers, most of whom were nurses. The sample was done by systematic sampling. Data collecting was done using questionnaires chi-square bivariate analysis and multivariate logistic regression. Qualitative research was done through interviews, focus group discussions and documentation with the status of 140 documents. The results of this quantitative study showed that the quality of study documentation in hospitals is still 80,3%, good category, and based on documentation study shows 52.9%. Meanwhile, as an information system between professionals was influenced by education, length of work, understanding of the Standard Operating Procedure (SOP) and concern of health professionals who write Patient Development Integrated Records, with the most dominant factor is the knowledge of SOP with (p=0.003). These factors should be a concern for the hospital management as the evaluation in order to improve care to patients, patient safety and protect health care workers from lawsuits.Keywords: Influential factor, Inter-professional information system, Patient development integrated records.